Population genomics of Plasmodium vivax in Panama to assess the risk of case importation on malaria elimination - Buyon, Lucas E.; Santamaria, Ana Maria; Early, Angela M.; Quijada, Mario; Barahona, Itza; Lasso, Jose; Avila, Mario; Volkman, Sarah K.; Marti, Matthias; Neafsey, Daniel E.; Obaldia III, Nicanor (PLoS neglected tropical diseases, 2020)
Malaria incidence in Panama has plateaued in recent years in spite of elimination efforts, with almost all cases caused by Plasmodium vivax . Notwithstanding, overall malaria prevalence remains low (fewer than 1 case per 1000 persons). We used selective whole genome amplification to sequence 59 P . vivax samples from Panama. The P . vivax samples were collected from two periods (2007–2009 and 2017–2019) to study the population structure and transmission dynamics of the parasite. Imported cases resulting from increased levels of human migration could threaten malaria elimination prospects, and four of the samples evaluated came from individuals with travel history. We explored patterns of recent common ancestry among the samples and observed that a highly genetically related lineage (termed CL1) was dominant among the samples (47 out of 59 samples with good sequencing coverage), spanning the entire period of the collection (2007–2019) and all regions of the country. We also found a second, smaller clonal lineage (termed CL2) of four parasites collected between 2017 and 2019. To explore the regional context of Panamanian P . vivax we conducted principal components analysis and constructed a neighbor-joining tree using these samples and samples collected worldwide from a previous study. Three of the four samples with travel history clustered with samples collected from their suspected country of origin (consistent with importation), while one appears to have been a result of local transmission. The small number of Panamanian P . vivax samples not belonging to either CL1 or CL2 clustered with samples collected from Colombia, suggesting they represent the genetically similar ancestral P . vivax population in Panama or were recently imported from Colombia. The low diversity we observe in Panama indicates that this parasite population has been previously subject to a severe bottleneck and may be eligible for elimination. Additionally, while we confirmed that P . vivax is imported to Panama from diverse geographic locations, the lack of impact from imported cases on the overall parasite population genomic profile suggests that onward transmission from such cases is limited and that imported cases may not presently pose a major barrier to elimination.